Antibiogram of chronic suppurative otitis media in relation to the current bacteriological profile in a tertiary care hospital - Iqbal, Naila; Anwar, Saba; Salim, Saira; Tehseen, Tahira; Ali, Saleha; Raza, Asif (Infectious Diseases Journal of Pakistan, 2024)
Background: Every year, about 31 million cases of chronic suppurative otitis media are reported. Due to a lack of access to healthcare, inadequate sanitation and hygiene standards, a lack of knowledge about ear care, underlying socioeconomic issues, and a lack of infrastructure for diagnosis and treatment, it is a common illness in low-income countries. The objective of this study is to determine the bacterial profile and susceptibility pattern of microorganisms isolated from chronic suppurative otitis media patients. Material and Methods: This Descriptive cross-sectional study was conducted at the Department of Microbiology, Izzat Ali Shah Hospital and POF Hospital Wah Cantt from December 2022 to January 2024. A total of 105 ear swabs were received for culture and sensitivity. Growth was observed in 70 ear swab cultures after 48 hours of incubation at 35±2ºC at ambient air. Isolates were identified as Staphylococcus aureus, Enterococcus spp, Enterobacterales including E. coli, Klebsiella pneumoniae, Proteus mirabilis, and Pseudomonas aeruginosa. Kirby Bauer disk diffusion method was used to assess susceptibility profiles of positive cultures using Muller Hinton agar incubated at a temperature of 35±2°C for 24 hours in ambient air. Results: Out of all 70 positive cultures, 40 isolates were gram-positive cocci while 30 isolates were gram-negative rods. In gram-positive isolates, Staphylococcus aureus was 90% susceptible to ampicillin while Enterococcus spp. was found to be 99% susceptible. Ampicillin was not tested for gram-negative organisms because of its proven inactivity against gram-negative bacteria. Susceptibility of Staphylococcus aureus was also tested against Penicillin and cefoxitin, where it was found to be 95% and 90% sensitive, respectively. Vancomycin was tested by minimum inhibitory concentrations using E-strip method. No resistance was observed in Staphylococcus aureus against vancomycin however, 0.5% vancomycin-resistant enterococcus spp were observed. Pseudomonas aeruginosa and Enterobacterales were found to have variable susceptibility to antimicrobials tested including Ceftazidime, Gentamicin, Imipenem, Ceftriaxone, cefepime, and Ciprofloxacin. Conclusion: Bacterial profile and susceptibility pattern of microorganisms isolated from chronic suppurative otitis media should be carried out routinely which can help establish an antibiogram as well as guide empirical therapies. Keywords: Antibiogram, Antibiotic stewardship, CSOM, Ear swab culture